Hypersensitivity and Chemotherapy Desensitization - Lawry, Dallas; Bell, Allegra; McKaig, Amanda; McParlane, Rayna (Seminars in oncology nursing, 2021)
Hypersensitivity reactions (HSRs) are defined as reactions with reproducible signs and symptoms, triggered by an exposure to a stimulus at a dose tolerated by normal subjects. Although discontinuing the allergenic medication can eliminate the potential for HSRs, it can also lead to significant morbidity and mortality due to suboptimal treatment of the underlying disease. Therefore, desensitization protocols have been developed that offer a safe process that delivers full therapeutic doses in an incremental fashion without eliciting life-threatening reactions. This article uses a case study to discuss the process of chemotherapy desensitization, associated complications, and identify areas of improvement in the management of HSRs within an academic medical center. HSRs are a complex pathophysiologic response that requires an experienced oncology nurse at the bedside to manage potentially life-threatening symptoms. Thorough education and training is needed among nursing staff to manage HSRs during the chemotherapy desensitization process.